The effects of prolonged CO 2 insufflation on kidney function in a rat pneumoperitoneum model - Dogan Yildirim; Turgut Donmez; Oguzhan Sunamak; Semih Mirapoglu; Adnan Hut; Nilgun Rukiye Erdogan; Zumrut Mine Isık Saglam; Huseyin Kilincaslan (Videosurgery and Other Miniinvasive Techniques)
Introduction : Pneumoperitoneum (PP) is known to cause ischemia in kidneys and other intra-abdominal organs because of decreased splanchnic blood flow. Aim : We aimed to determine the degree of renal injury that occurs due to a PP and prolonged PP. We measured renal injury biomarkers and made a histopathological evaluation to estimate the degree of injury and assessed the correlation of biomarkers with histopathological findings. Material and methods : Twenty-one female Sprague Dawley rats were separated randomly into three groups. Group 1 was the control group and was given anesthesia for 3 h. In group 2, a PP was administered under anesthesia for 1 h. A pneumoperitoneum was administered under anesthesia to animals in group 3 for 3 h. Results : Pathological analysis showed a significant statistical difference between the 3 groups. In particular, neutrophil gelatinase-associated lipocalin (NGAL) and cystatin C (Cys C) levels at the 24th h and preoperative mean urea levels showed a significant difference between the groups. The 24th-hour NGAL level in group 3 was significantly higher than that of group 1. The preoperative Cys C level was higher in group 1 than in either group 2 or 3. Cys C was decreased significantly in group 1 and increased significantly in both groups 2 and 3. Conclusions : The increase in NGAL and Cys C levels directly correlated with the duration of PP and intra-abdominal pressure, and they are therefore good biomarkers in diagnosing acute renal injury in the early phase. Serum creatinine level is not a good biomarker in the early phase of renal injury.